2011
DOI: 10.1371/journal.pone.0024515
|View full text |Cite
|
Sign up to set email alerts
|

CHD5, a Brain-Specific Paralog of Mi2 Chromatin Remodeling Enzymes, Regulates Expression of Neuronal Genes

Abstract: CHD5 is frequently deleted in neuroblastoma and is a tumor suppressor gene. However, little is known about the role of CHD5 other than it is homologous to chromatin remodeling ATPases. We found CHD5 mRNA was restricted to the brain; by contrast, most remodeling ATPases were broadly expressed. CHD5 protein isolated from mouse brain was associated with HDAC2, p66ß, MTA3 and RbAp46 in a megadalton complex. CHD5 protein was detected in several rat brain regions and appeared to be enriched in neurons. CHD5 protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
91
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(105 citation statements)
references
References 60 publications
(92 reference statements)
13
91
0
1
Order By: Relevance
“…In trisomy 21, however, DYRK1A is dysregulated, thereby leading to increased expression of NRSF/REST, subsequent disturbances in NRSF/REST-SWI/SNF complex assembly, and deficits in dendritic growth/complexity in the adult brain. Taken together, these data, along with findings demonstrating the existence of brain-specific/-restricted chromatinremodeling proteins (eg, CHD5, a remodeling ATPase known to interact with HDAC2, which has been linked to gene expression patterns associated with aging and Alzheimer's disease) (Potts et al, 2011), demonstrate that regulatory control over chromatin-remodeling activities/ enzymes in the adult CNS is important to numerous aspects of adult neurological function; however, dissecting the developmental vs adulthood contributions of such complexes to neuropsychiatric disease remains difficult.…”
Section: Atp-dependent Chromatin Remodeling: Relevance To Neurologicasupporting
confidence: 55%
“…In trisomy 21, however, DYRK1A is dysregulated, thereby leading to increased expression of NRSF/REST, subsequent disturbances in NRSF/REST-SWI/SNF complex assembly, and deficits in dendritic growth/complexity in the adult brain. Taken together, these data, along with findings demonstrating the existence of brain-specific/-restricted chromatinremodeling proteins (eg, CHD5, a remodeling ATPase known to interact with HDAC2, which has been linked to gene expression patterns associated with aging and Alzheimer's disease) (Potts et al, 2011), demonstrate that regulatory control over chromatin-remodeling activities/ enzymes in the adult CNS is important to numerous aspects of adult neurological function; however, dissecting the developmental vs adulthood contributions of such complexes to neuropsychiatric disease remains difficult.…”
Section: Atp-dependent Chromatin Remodeling: Relevance To Neurologicasupporting
confidence: 55%
“…Another interaction level may be convergence of signals downstream of 1p36 genes on identical pathways. In an adequate cellular context, CHD5, CAMTA1, CASZ1, and miR-34a all activate genetic programs implicated in neuronal function and differentiation (31,55,75,120). Expression of neuronspecific gene sets is associated with a markedly better prognosis in both neuroblastomas and gliomas (68,121,122).…”
Section: Discussionmentioning
confidence: 99%
“…CHD5 resides in 1p36.31, is preferentially expressed in neuronal tissues, and its product regulates genes involved in neuronal function, cell-cycle control, and chromatin remodeling (31). Functional evidence for a tumor suppressive role of mouse Chd5 derives from an elegant approach using chromosome engineering to generate mouse models with loss or gain of genomic regions corresponding to human 1p36 (22).…”
Section: Chd5mentioning
confidence: 99%
“…Alternatively, MBD3/NuRD may be the principal form of NuRD in the brain, as it is expressed in this tissue (Figure 8) and other studies have shown that it affects synaptic connectivity in addition to regulating cortical neuronal differentiation [33,34]. A related explanation for absence of significant MBD2-dependent brain function is that a brain-specific, alternate form of NuRD that interacts with MBD3, but not MBD2, may be acting predominantly in the brain in vivo [36].…”
Section: Discussionmentioning
confidence: 97%
“…Mbd1 knockout mice also exhibit behavioral phenotypes that mimic features of ASD such as learning and memory deficits, reduced sociability, and changes in anxiety-related phenotypes [22,29]. Furthermore, MBD3 and multiple components of the MBD-associated corepressor complexes, such as NuRD, Sin3A and NCoR/SMRT, also have critical roles in the brain [33][34][35][36][37]. Given the similarities between the MBD proteins, it has been postulated that MBD2 may also have a role in brain function [6].…”
mentioning
confidence: 99%